Transformasi Sumber Daya Manusia Protokol Pemerintahan melalui Komunikasi Digital dan Artificial Intelligence: Analisis Bibliometrik - Anna Asriniati Harahap (Kampus Akademik Publiser, 2026)
Digital transformation has driven a paradigm shift in public sector human resource management, particularly through the utilization of digital communication and Artificial Intelligence (AI). This study aims to map research developments, knowledge structures, scientific collaboration patterns, and future directions of studies on the transformation of government protocol human resources through digital communication and Artificial Intelligence. The research employs a quantitative approach using bibliometric analysis methods. Research data were obtained from the Dimensions database using relevant keywords, yielding 5,652 publications analyzed using VOSviewer software. The analysis was conducted through network visualization, overlay visualization, density visualization, as well as analyses of author productivity, organizations, countries, and publication trends. The findings indicate that the development of this research domain is dominated by themes such as innovation, artificial intelligence, communication, application, platform, public administration, and digital governance. The network visualization identified three main interconnected clusters, while the trend analysis revealed a shift in research focus from e-government toward the utilization of AI, digital platforms, cybersecurity, and disinformation. Furthermore, the analysis results show the formation of extensive international collaboration networks among authors, organizations, and countries. This study concludes that public sector human resource transformation is evolving as a multidisciplinary field of inquiry that integrates public administration, digital communication, governance, organizational innovation, and Artificial Intelligence. The research findings provide a knowledge map that can serve as a foundation for the development of future research and policy on government digital transformation.